Pengaruh DER, PER Dan ROA Terhadap PBV Pada Industri Perbankan - Iwan Firdaus (Jurnal Ekonomi, 2019)
This research is to find out the influence of DER, PER and ROA to PBV in the banking industry published on Indonesia Stock Exchange for the period 2013-2017. Sample selection with purposive sampling method as many as 21 companies, totalling 105 data. The method used in this research is panel data regression analysis and it is found that the more appropriate model used is a fixed effect. From the result of the research got the value of adjusted R-Square is equal to 15.86%. Partially show that DER, PER variable have a positive and significant effect on PBV. ROA variable partially has positive and no significant effect on PBV.